Uso de polimixina em pacientes submetidos a transplante: avaliação de eficácia e nefrotoxicidade - Mostardeiro, Marcelo Mileto [UNIFESP] (2009)
Introduction: Polymyxins are old antimicrobials which had their use discontinued for many years because of nephrotoxicity and neurotoxicity description. The development of multirresistant gram negative bacteria in special P aeruginosa and A baumanii all over the world is a matter of fact and we have observed its growth in international epidemiologic surveys since the 90’s. Until now we don´t have studies that demonstrate renal dysfunction tax in transplanted patients because of polymyxin use, nevertheless we know that renal function contribute in a statistical significant manner for receptors survive in long term. Methods: We have retrospectively searched for all solid organ transplanted patients and who have used polymyxins from January 2001 to December 2007 in 2 teaching hospitals in São Paulo city, Brazil. The main study objective was to define the nephrotoxicity percentage. For evaluating this variable we choosed 2 renal function definitions (first criteria and second criteria) and applied them in all studied patients with the objective of comparing them each other and with the literature. First criteria was defined as serum creatinine > 2 mg/dl after polymyxin introduction in those patients with acute renal dysfunction, or 50% serum creatinine increase in relation to value before polymyxin was given in those patients with previous nephotoxicity. In both situations described above we also considered renal dysfunction if 50% decrease in estimated creatinine clearance by Cockcroft & Gault methodology occurred, or progression to dialysis therapy. Second criteria was defined as any serum creatinine increase. Results: We identified 92 solid organ transplanted patients who used polymyxins. The majority of them received renal or renal/pancreas grafts (90.2%), and the organs transplanted were from deceased donors in 70,7%. The main site of infection were urinary tract infection (UTI) (41.3%), followed by surgical site infection (SSI) (17.4%) and pneumonia (16.3%). P aeruginosa were the main etiologic agent present in 76.1% of isolates. Microbiologic cure occurred in 25 patients (100%), clinical cure in 71 patients (77.2%), and in hospital mortality occurred in 21 patients (22.8%). Fourty four patients (47.8%) presented nephrotoxicity according to any of the 2 adopted criteria, 30 patients (32.6%) according to the first criteria, and 44 patients (47.8%) according to the second criteria. Multivariate analysis show statistical significant association among UTI and protection for renal dysfunction [p 0.02; OR 0.24; IC 95% (0.07 – 0.86)], and greater mean polymyxin utilization time (p 0.03) as a risk factor for renal dysfunction by the first criteria. Conclusions: The 32.6% percentage of renal dysfunction is still high, but lower than that reported in the 60’s and 70’s. Polymyxin utilization is effective principally for the treatment of UTI in solid organ transplanted patients, its use should be judicious and for shorter time as possible.